Long-term Impact of Pneumococcal Conjugate Vaccines on Invasive Disease and Pneumonia Hospitalizations in Indigenous and Non-Indigenous Australians. (7th August 2019) - Meder, Kelley N; Jayasinghe, Sanjay; Beard, Frank; Dey, Aditi; Kirk, Martyn; Cook, Heather; Strachan, Janet; Sintchenko, Vitali; Smith, Helen; Giele, Carolien; Howden, Benjamin; Krause, Vicki; et al.
Abstract: Background: Universal pneumococcal conjugate vaccine (PCV) programs began in Indigenous Australian children in 2001 and all children in 2005, changing to 13-valent PCV (PCV13) in 2011. We used laboratory data for invasive pneumococcal disease (IPD) and coded hospitalizations for noninvasive pneumococcal community-acquired pneumonia (PnCAP) to evaluate long-term impact. Methods: Annual incidence (per 100 000 population) was calculated for age-specific total IPD, PCV13 non–7-valent PCV (PCV7) serotypes, and PnCAP by Indigenous status. Incidence in the pre–universal PCV7 (2002–2004), early PCV7 (2005–2007), pre-PCV13 (2008 to mid-2011), and post-PCV13 (mid-2011 to 2016) periods was used to calculate incidence rate ratios (IRRs). Results: In the total population, all-age incidence of IPD declined from 11.8 pre-PCV7 to 7.1 post-PCV13 (IRR, 0.61 [95% confidence interval CI, .59–.63]) but for PnCAP declined among ages <1 year (IRR, 0.34 [95% CI, .25–.45]) and 1–4 years (IRR, 0.50 [95% CI, .43–.57]) but increased significantly among age ≥5 years (IRRs, 1.08–1.14). In Indigenous people, baseline PCV13 non-PCV7 IPD incidence was 3-fold higher, amplified by a serotype 1 epidemic in 2011. By 2015–2016, although incidence of IPD and PnCAP in children aged <5 years decreased by 38%, neither decreased in people aged ≥5 years. Conclusions: Fifteen years post-PCV and 5 years post-PCV13, direct and indirect impact on IPD and PnCAP differed by age and between Indigenous and non-Indigenous people, with potential implications for long-term PCV impact in comparable settings. Fifteen years after pneumococcal conjugate vaccine (PCV) introduction and 5 years post-PCV13, direct and indirect impact on invasive pneumococcal disease and pneumococcal community-acquired pneumonia differed by age and between Indigenous and non-Indigenous people, with potential implications for long-term PCV impact in comparable settings.